Plan de seguridad para la práctica de actividades turísticas en las siete cascadas del Zapanal. - Quillupangui Toapanta, Nancy Veronica (2020)
Insecurity in the practice of tourist activities in the seven waterfalls from el Zapanal located in the “La Envidia” village influenced to design a security plan for the minimization and accident prevention since natural attractiveness lacks safety measures and standards tourism that contribute to the physical and psychological protection of visitors. The methodology applied consisted of six field trips collecting primary information through interviews, surveys aimed at the people involved allowing to establish a current diagnosis of the location as well as the recognition of the current path was made identifying and geo referencing 7 fragile or higher risk points and 43 signage needs and same tourist structures that were designed according to the surveys applied to visitors and under the regulations of the tourist signage manuals by the Ministry of Tourism of Ecuador, signage for the heritage of natural areas of the State, tourist signage in CONGOPARE rural areas and the trail and public use manual. It was subsequently generated a security plan with the information obtained in which 5 strategies are established for security according to the reality of the place involving public and private tourism participants, highlighting the following strategies: linking the public sector in the tourism field, strengthening tourism security for the practice of activities, strengthening of information and tourist orientation, provision of first aid equipment in the seven waterfalls, control and monitoring of tourist activities to operators and travel agencies for tourist activities. Strengthening the security and image of natural attractiveness will benefit the community and visitors where the waterfalls are generating positive in the technical, social, economic and environmental field guaranteeing sustainable tourism development.